Industrial Applications of Nanoparticles – A Prospective Overview. (2015) - Santos, Cátia S.C.; Gabriel, Barbara; Blanchy, Marilys; Menes, Olivia; García, Denise; Blanco, Miren; Arconada, Noemí; Neto, Victor
Abstract: Nanotechnology describes the characterization, fabrication and manipulation of structures, devices or materials that have one or more dimensions that are smaller than 100 nanometers. This area has established itself as a key enabling technology for a wide range of applications, thus becoming a top priority for science and technology policy development, being already used in hundreds of products among the industrial sector, namely, electronic, healthcare, chemical, cosmetics, composites and energy. Despite the development in this area, there are some obstacles to a greater impact of nanotechnology in industry. The lack of information concerning this scientific area, the possibility of adverse impacts of nanotechnology on the environment, human health, safety and sustainability, are still a challenge. This article intends to briefly the prototypes being developed with in the CarbonIspired 2.0 consortium, given with them examples of practical applications, security issues and market challenges in order to an effective collaboration between the academies, research centers and the industrial sector.